Strategi Komunikasi Antarpribadi Guru dalam Menghadapi Temper Tantrum pada Siswa SLB-E Pembina Tingkat Provinsi Kota Medan - Harahap, Namira Azzahra (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
This research is based on problems that researchers found in the field which shows how important the role of a teacher is in contributing to the formation of children's character at school. Temper tantrums are destructive behavior, in the form of outbursts which can be physical such as hitting, pushing, slamming an object or in verbal form, such as screaming, crying, screaming or whining. One way that can be used to overcome temper tantrums is to let them do what they want until they get tired and stop by themselves. The aim of this research is to find out the role of teachers in dealing with children with temper tantrums. This research method is descriptive qualitative. Data was collected through observation, documentation and teacher interviews at school. Data is analyzed using data reduction, displaying data and drawing conclusions. The results of this research regarding Teacher Communication Strategies for Students with Autism at SLB – E E Pembina Level Medan City really have a positive influence on children. This research shows that the process of handling children who experience tantrums is to give them space to express themselves and express their emotions until they are satisfied and make the child calmer, their emotions more controllable and able to accept the handling stimuli given by other people to the child.